Entrepreneurship pedagogy enhancing entrepreneurship intention in secondary school students in developing countries - Eunah, Kakava; Eta, Marima Nelia; Shepherd, Murebwa (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aims to investigate entrepreneurship pedagogy to enhance entrepreneurship intention among secondary school students. Research methodology: The researchers self-administered 100 questionnaires to educators in secondary schools in Gweru Urban Schools, obtaining a response rate of 92%. Quantitative data were analyzed using regression to establish a relationship between entrepreneurship pedagogy and entrepreneurship intention. Results: Results showed that entrepreneurship Experiential learning was positively correlated with entrepreneurship intention. In addition, the results showed that entrepreneurship design thinking, problem-based learning, and collaborative pedagogy were positively correlated with entrepreneurship intention. Limitations: This study faced methodological constraints because it used a population from an urban setting. However, further studies covering developing countries in Africa are recommended.   Contribution:  This study contributes to policy and curriculum changes in the way entrepreneurship pedagogies are implemented in developing countries. Novelty: This study integrates entrepreneurship pedagogies applicable to entrepreneurship education to achieve entrepreneurship intention in secondary schools in developing countries using Sociocultural Theory.